2010
DOI: 10.1177/0022466910366602
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Teacher Practice in Queensland Transition Programs for Youth With Intellectual Disability and Autism

Abstract: Extensive work has been done in North America to examine practices recommended to facilitate postschool transitions for youth with disabilities. Few studies in Australia, however, have investigated these practices. This study drew on the Taxonomy for Transition Programming developed by Kohler to benchmark practice at government and nongovernment schools throughout Queensland, Australia. A statewide survey was used to gather data from teachers and other influential staff (N = 104). Participants were asked to (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…However, the varied experiences of the participating parents indicate that these practices are inconsistent at best. This finding is consistent with the findings of a study conducted by Beamish, Meadows, and Davies (2012), who surveyed 104 teachers in Queensland, Australia, on their use of research-based practices comprised in Kohler's taxonomy. The results indicated that areas of interagency collaboration and programme structure had lower levels of endorsement and implementation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the varied experiences of the participating parents indicate that these practices are inconsistent at best. This finding is consistent with the findings of a study conducted by Beamish, Meadows, and Davies (2012), who surveyed 104 teachers in Queensland, Australia, on their use of research-based practices comprised in Kohler's taxonomy. The results indicated that areas of interagency collaboration and programme structure had lower levels of endorsement and implementation.…”
Section: Discussionsupporting
confidence: 90%
“…The findings from this study highlight the significance of effective interagency and interdisciplinary collaboration as specified in Kohler's taxonomy. For interagency and interdisciplinary collaboration to be effective, there is a need for clearly defined roles and responsibilities (Beamish, Meadows, and Davies 2012), coordinated and shared delivery of transition-related services, and collaborative funding and staffing of transition services (Kohler 1996;Kohler and Field 2003). However, the varied experiences of the participating parents indicate that these practices are inconsistent at best.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, these countries made several amendments on their policies to give more financial support and develop different programs to make access realistic to learner. Ireland was among the first one to develop special needs act in 2004 even before adoption of CRPD in 2006 (Kavouni, 2016;Clerke, 2015;Beamish, W., Meadows, D.,& Davies, 2010;Watson, 2009;Foloştină, Duţă, & Prăvălici, 2014;Zvoleyko, Kalashnikova, & Klimenko, 2016;Louise, 2013;Karr, Valerie L.Edema, Ashley van Sims, Jacob Brusegaard, 2017;Callan & Ed, 2018;UNESCO, 2015;WHO, 2011;and WB, 2015).…”
Section: Development Of Disability Policies On Access To Educationmentioning
confidence: 99%
“…Como se ha comentado anteriormente, estas propuestas han sido una constante en la literatura de transición (Tabla 1). Una de las primeras es la Taxonomy for Transition Programming (Kohler, 1996), que se ha mantenido a lo largo de los años y diversos autores la siguen considerando como el único modelo de transición basado en evidencias empíricas (Beamish, Meadows y Davies, 2010;Test, Aspel y Everson, 2006). Años después Kohler y Field (2003), tras recalcar la importancia del sistema educativo en el inicio de los procesos de planificación de la transición, revisan y actualizan el modelo conceptual de Kohler (1996) y vuelven a proponer las cinco áreas de la Taxonomía como síntesis de las aportaciones de la investigación.…”
unclassified